Sensory–Motor Polyneuropathy in an 11-year- old Girl with a Pathogenic Variant in SMC1A: A Case Report - De Luisa, Angelica; Cesaroni, Carlo A.; Pollazzon, Marzia; Spagnoli, Carlotta; Caraffi, Stefano G.; Leon, Alberta; Rizzi, Susanna; Frattini, Daniele; Cavalli, Anna; Garavelli, Livia; Fusco, Carlo (Neuropediatrics, 2024)
Pathogenic variants in the SMC1A gene are often dominant-negative and cause an X-linked form of Cornelia de Lange syndrome (CdLS) with growth retardation and typical facial features. However, rare SMC1A variants cause a developmental and epileptic encephalopathy (DEE) with intractable early-onset epilepsy that is absent in CdLS. Here we describe an 11-year-old girl with epilepsy, walking disorder, and neurodevelopmental disorder. A neurophysiological examination of nerve conduction velocity showed a mixed, sensory–motor, chronic 4-limb polyneuropathy. Whole-exome sequencing identified the variant c.3145C > T p.(Arg1049*) in SMC1A (NM_006306.3), which can be classified as pathogenic. To the best of our knowledge, among 79 individuals with SMC1A-related DEE reported in the literature, altered peripheral nerve conduction has never been described. In this article, we propose that severe sensory–motor polyneuropathy could be an expansion of the SMC1A-related phenotype.
Keywords: SMC1A; epilepsy; neurodevelopmental disorder; neuropathy